Effect of (Nees) Radlk fresh leaf ethanolic extract on human breast cancer MDA-MB-231 regulated cell death - Phimphan Komonrit; Ratana Banjerdpongchai (Tumor Biology)
Leaf extracts of Pseuderanthemum palatiferum (Nees) Radlk were investigated for their effects on human breast cancer MDA-MB-231 cell growth inhibition. Pseuderanthemum palatiferum (Nees) Radlk extracts were prepared using fresh or dried leaves and extracted by either water or 95% ethanol, respectively. Fresh leaf ethanolic extract was the most toxic to MDA-MB-231 cells measured by 3-(4,5-dimethyl)-2,5-diphenyl tetrazolium bromide assay. Fresh leaf ethanolic extract–treated MDA-MB-231 cell death was stained with propidium iodide and examined under fluorescence microscopy. Cell death was confirmed by annexin V-fluorescein isothiocyanate/propidium iodide and propidium iodide–stained cells employing flow cytometry. The mitochondrial transmembrane potential was disrupted in fresh leaf ethanolic extract–treated MDA-MB-231 cells and the percentage of cells with reduced mitochondrial transmembrane potential increased according to concentrations. Mitochondrial transmembrane potential–driven regulated cell deaths were in the form of both apoptosis and necrosis. Oxidative stress probe, 2′,7′-dichlorodihydrofluorescein diacetate, was used to indicate the redox status. Dichlorofluorescein level was significantly lower at high fresh leaf ethanolic extract concentrations. Total phenolic contents were found in all Pseuderanthemum palatiferum (Nees) Radlk extracts, whereas Ca 2+ level in the cytosol increased, indicating Ca 2+ overload and endoplasmic reticulum stress involvement with the activation of caspase-3, -8, and -9. In conclusion, fresh leaf ethanolic extract induced human breast cancer MDA-MB-231 programmed cell death via endoplasmic reticulum and oxidative stress by activating both extrinsic and intrinsic signaling pathways.